أثر مقياسي الخطأ الشعاعي والثابت في دقة اداء الهجوم البسيط للاعبي المبارزة بسلاح الشيش - متعب, سامر يوسف; هادي, حامد عبد الشهيد (Sulaimani Journal for Humanities, 2018)
The fencing is one of the difficult singular game which require many high requirements from the players like the motor control in skill performance to able to performed it in high accuracy due to the fencing depend on attack with accuracy on special places . Therefore, the trainer should use the modern methods and means, which help players for, develop the performance accuracy, especially the appeal skill. The performance of appeals relative with success and errors in result of all attempt, مجلة )زانکۆی سلێمانی( القسم )B )للدراسات االنسانیة – العدد )65( عدد خاص لمؤتمر الدولي األول لكلیة التربیة الرياضية 676 so we should benefit completely from errors as well as the success but we can get more benefits from the errors more than the success for learning and training possess because it contain different characteristics of real performance and the reasons behind. If trainer discover them, be able to deal with the errors and raise the level of skill performance Through the follow of researchers for the junior fencing players of notices there was weak in accuracy of simple attack (the direct straight attack-the attack with turn direction- the cross attack) therefor the researchers tried to benefit from the new style which afford from magill in his last book, how to deal with the error measures and benefit from these ideas to discover the reasons errors to treat them according to the individual differentness of sample. The aims of study was development the simple attack performance for fencing players in foil weapon , and design new tests to measure redial and constant error. The hypotheses was; there was a significant differences between the experimental and control group in performance of simple attack. The population of research was the junior players in dayala city clubs, and the sample represented the whole population. The most important conclusions was; there was a significant effects for use the redial and constant error measures for development the performance accuracy of simple attack.
Keywords: fencingsimple attackredial and constant error measures